Analisis Modal Kerja Pada PT. Kawasan Industri Makassar (Persero) Tahun 2019-2021 - Anggi Astika; Sabirin Iskandar; Nurmega Nurmega (Universitas Kristen Indonesia Toraja, 2024)
This research aims to find out whether the working capital ratio is able to measure the financial performance of PT Kima in 2019-2021. The object of this research is PT KIMA. The data used is primary data. The sample in this research is PT KIMA's financial report for the 2019-2021 period. The results of this research show that the calculation of financial data using activity ratio analysis, profitability ratios (Return On Assets), solvency and profitability ratios, the company's working capital at PT. company to pay dividend payout ratio (DPR) to shareholders. Meanwhile, the profitability ratio (Net Profit Margin) can be said to be good because the net profit value obtained from sales, which includes production costs, will increase profits for the company.